DIGITAL EXHIBITION ENHANCE VALUE INTERPRETATION AND COMMUNITY SHARING: PRACTICES OF BEIJING CENTRAL AXIS - Y. He; N. Peng; W. Li; Y. Tai (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
The use of multiple digital technologies has addressed conventional exhibition display issues, improving public experience, and aiding in the understanding of historical changes in cultural heritage. This facilitates community sharing and international promotion. Furthermore, the promotion of novel digital application scenarios can encourage the growth of cultural consumption and the digital creativity industry. Beijing's Central Axis is a remarkable and well-preserved example of a traditional central axis in China's capital cities. It is comprised of numerous building complexes and archaeological sites located within the old city. This axis was first constructed in the 13th century, shaped in the 16th century, and continues to thrive today while remaining open to the future. By assessing its dynamic "growth" and "living" value, we have devised an innovative interpretation system plan that includes Augmented Reality Tours, immersive exhibitions in historical buildings, online exhibitions, and a series of public activities. The pilot project, implemented at the Drum Tower located at the northern end of the Central Axis, involved careful restoration and scientific transformation, accurate heritage documentation, and digital reconstruction. Digital creativity empowered and activated the historical building, achieving a comprehensive balance of conservation, utilization, and economics. The exhibition has garnered favorable feedback, particularly from the younger generation, who appreciate the combination of ancient cultural heritage themes and modern digital immersive displays.